Constructing Conflict: A Review Essay - Carnahan, Kevin (Journal of law and religion, 2013)
Review of: CRESCENT AND DOVE: PEACE AND CONFLICT RESOLUTION IN ISLAM. Edited by Qamar-Ul Huda. United States Institute of Peace Press 2010. Pp.336. $24.05. ISBN: 1-601-27060-7; JUST WAR ON TERROR! A CHRISTIAN AND MUSLIM RESPONSE. Edited by David Fisher and Brian Wicker. Ashgate2010. Pp.240. $29.95. ISBN: 1-409-40808-6; ISLAMIC LAW AND THE LAW OF ARMED CONFLICT: THE ARMED CONFLICT IN PAKISTAN. By Niaz Shah. Routledge 2011. Pp.176. $110.56. ISBN: 0-415-56396-8.